Comparative effectiveness research using electronic health records: impacts of oral antidiabetic drugs on the development of chronic kidney disease. (24th February 2013) - L. Masica, Andrew; Ewen, Edward; A. Daoud, Yahya; Cheng, Dunlei; Franceschini, Nora; E. Kudyakov, Rustam; R. Bowen, James; Brouwer, Emily S.; Wallace, Dennis; S. Fleming, Neil; West, Suzanne L.
ABSTRACT: Purpose: Little is known about the comparative effects of common oral antidiabetic drugs ([OADs] metformin, sulfonylureas, or thiazolidinediones [THZs]) on chronic kidney disease (CKD) outcomes in patients newly diagnosed with type 2 diabetes (T2DM) and followed in community primary care practices. Electronic health records (EHRs) were used to evaluate the relationships between OAD class use and incident proteinuria and prevention of glomerular filtration rate decline. Methods: A retrospective cohort study on newly diagnosed T2D cases requiring OADs documented in the EHRs of two primary care networks between 1998 and 2009 was conducted. CKD outcomes were new‐onset proteinuria and estimated GFR (eGFR) falling below 60 ml/min/1.73 m 2 . OAD exposures defined cohorts. Hazard ratios represent differential CKD outcome risk per year of OAD class use. Results: A total of 798 and 977 patients qualified for proteinuria and eGFR outcome analyses, respectively. With metformin as the reference group, sulfonylurea exposure trended toward association with an increased risk of developing proteinuria ([adjusted hazard ratio; 95% CI] 1.27; 0.93, 1.74); proteinuria risk associated with THZ exposure (1.00; 0.70, 1.42) was similar to metformin. Compared with metformin, sulfonylurea exposure was associated with an increased risk of eGFR reduction to <60 ml/min/1.73 m 2 (1.41; 1.05, 1.91). THZ exposure (1.04; 0.71, 1.50) was not associated with change in the risk of eGFR decline. Conclusions: In a primary care population, metformin appeared to decrease the risk of CKD development compared with sulfonlyureas; risks of CKD development between metformin and THZs were similar. EHR use in pharmacotherapy comparative effectiveness research creates specific challenges and study limitations. Copyright © 2013 John Wiley & Sons, Ltd.